2013
DOI: 10.1016/j.geomorph.2013.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Origin of step-like and lobate seafloor features along the continental shelf off Rio de Janeiro State, Santos basin-Brazil

Abstract: International audienceA combined analysis of seismic and morphological features identified in a set of high-resolution seismic reflection and bathymetric data, shows a systematic relationship between major modern seafloor morphological traces and the basinward migration of Late Pleistocene coastlines along the continental shelf of the Santos basin (Rio de Janeiro State, SE Brazil). Observed fairly continuous and sinuous mid-outer shelf escarpments are related to the sea-level variations and shelf exposure duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 51 publications
1
34
0
15
Order By: Relevance
“…13D). In many areas of the Brazilian coast (Martin and Suguio, 1992;Angulo et al, 2006;Rossetti et al, 2008;Reis et al, 2013) and of the South American coast (Milne et al, 2005), the sea level surpassed the present at 7000 yr BP (Suguio et al, 1985) by 4 to 6 m. The transgressive deposits of phase 1 could be taken as a further evidence of sea levels above the present level along the Brazilian coast near the early to mid-Holocene.…”
Section: Sea-level Historymentioning
confidence: 94%
See 1 more Smart Citation
“…13D). In many areas of the Brazilian coast (Martin and Suguio, 1992;Angulo et al, 2006;Rossetti et al, 2008;Reis et al, 2013) and of the South American coast (Milne et al, 2005), the sea level surpassed the present at 7000 yr BP (Suguio et al, 1985) by 4 to 6 m. The transgressive deposits of phase 1 could be taken as a further evidence of sea levels above the present level along the Brazilian coast near the early to mid-Holocene.…”
Section: Sea-level Historymentioning
confidence: 94%
“…11. Summary of the deltaic prograding events 1 to 3 in the study area within the context of sea-level changes proposed by previous publications for the study area and worldwide during the Late Pleistocene-Holocene (modified from Lambeck and Chappell, 2001;Reis et al, 2013). Data from Bard et al (1990), Bassinot et al (1994), Chappell and Shackleton (1986), Imbrie (1984), Labeyrie et al (1987), Lambeck (1997), Rohling et al (1998), Siddall et al (2003, Skene (1998) and Toscano and Lundberg (1999).…”
Section: Sea-level Historymentioning
confidence: 96%
“…A continued river sediment supply may result in shoreline progradation, and it can generate a delta (Suter, 1994). Considering the relative sea-level changes during the Holocene, it crossed above the present one at 7000 BP (Suguio et al, 1985), reaching 4 to 6 m above the present one in many areas of the Brazilian coast (Martin and Suguio, 1992;Angulo et al, 2006;Rossetti et al, 2008;Reis et al, 2013), with a subsequent fall to the present time (e.g., Angulo et al, 2006). In terms of climatic changes, significant rainfall variations occurred in the Brazilian central region, and consequently it affected the volume of the rivers.…”
Section: Introductionmentioning
confidence: 94%
“…Also, it clearly showed the expansion of the Tropical clade starting approximately 50 kyr ago reaching demographic stability at the end of last glacial maximum (~10 kyr ago). This period was characterized by secondary extreme and short-lived events (known as Heinrich events), where temperature drop-offs and sea level fluctuations, reached 130 m lower than today (Adams et al, 1999;Chappell and Shackleton, 1986;Reis et al, 2013;Rossetti et al, 2015). Such severe climatic and sea level fluctuations during the late Pleistocene (Adams et al, 1999) have been suggested as strong influence in shaping patterns of genetic variability and the geographic distribution of marine fauna (Almada et al, 2001;Domingues et al, 2006Domingues et al, , 2007aDomingues et al, , 2007bSantos et al, 2006;Stefanni et al, 2006).…”
Section: Discussionmentioning
confidence: 99%